Metal-Organic Frameworks and Their Composites Towards Biomedical Applications - Ma, Yana; Qu, Xianglong; Liu, Cui; Xu, Qiuran; Tu, Kangsheng (Frontiers in Molecular Biosciences, 2021)
Owing to their unique features, including high cargo loading, biodegradability, and tailorability, metal-organic frameworks (MOFs) and their composites have attracted increasing attention in various fields. In this review, application strategies of MOFs and their composites in nanomedicine with emphasis on their functions are presented, from drug delivery, therapeutics agents for different diseases, imaging contrast agents, to sensor nanoreactors. Applications of MOF-derivatives in nanomedicine are also introduced. Besides, we summarize different functionalities related to MOFs, which include targeting strategy, biomimetic modification, responsive moieties, and other functional decoration. Finally, challenges and prospects are highlighted about MOFs in future applications.